2018
DOI: 10.1002/biot.201800024
|View full text |Cite
|
Sign up to set email alerts
|

Move to Nano‐Arthrology: Targeted Stimuli‐Responsive Nanomedicines Combat Adaptive Treatment Tolerance (ATT) of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is one of the most popular chronic autoimmune diseases characterized with persistent synovial inflammation and bone destruction. Although considerable developments have been gained in clinical treatment of RA, the major drawback to RA therapy stems from the adaptive treatment tolerance (ATT) following the long-term drug use, which causes compromised efficacy, sustained drug dose increase, and severe adverse events. To address these challenges, it is of great significance to put forwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 109 publications
0
12
0
Order By: Relevance
“…Overall, both forms of arthritis are complex processes driven by multiple inflammatory and metabolic factors. For instance, the risk factors for inflammatory OA include aging, obesity, joint trauma, repetitive activity, etc., whereas the risk factors for RA include genetic, immune, and environmental factors, among others [ 7 , 8 ]. In most cases, the two forms of arthritis share corporate disease features, including monocyte infiltration, inflammation, synovial swelling, vascular pimple formation, joint stiffness, and articular cartilage destruction [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, both forms of arthritis are complex processes driven by multiple inflammatory and metabolic factors. For instance, the risk factors for inflammatory OA include aging, obesity, joint trauma, repetitive activity, etc., whereas the risk factors for RA include genetic, immune, and environmental factors, among others [ 7 , 8 ]. In most cases, the two forms of arthritis share corporate disease features, including monocyte infiltration, inflammation, synovial swelling, vascular pimple formation, joint stiffness, and articular cartilage destruction [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sumbayev et al 46 observed that AuNPs down‐regulate IL‐1β in vivo. Feng et al and Liu et al 5 referred to the interference of AuNPs in inflammatory signalling and reduced inflammatory cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies over a long period gave great attention to RA to develop an effective treatment. Rheumatoid arthritis therapeutic agents are classified into four categories: disease‐modifying anti‐rheumatic drugs (DMARDs), glucocorticoids (GCs), non‐steroidal anti‐inflammatory drugs (NSAIDs) and newly discovered biological agents 5 . Unfortunately, several drawbacks are still present, including undesirable side effects that accompany traditional treatment, high risk of therapeutic tolerance and dysfunction stimulated by ascending doses.…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable progress has been made in the clinical treatment of RA, the adaptive treatment tolerance (ATT) remains to be a major concern. Thus, Xing‐Jie Liang and Weisheng Guo highlight current research of targeted stimuli‐responsive nanomedicines for RA therapy which will pave the way to novel and highly effective RA nanomedicine …”
mentioning
confidence: 99%
“…Thus, Xing-Jie Liang and Weisheng Guo highlight current research of targeted stimuli-responsive nanomedicines for RA therapy which will pave the way to novel and highly effective RA nanomedicine. [4] Also further articles are highlighting biomaterials research and nanomaterials: Spider silks have received considerable attention and have been proposed to be ideal substances for biomedical applications; however, limited supply remains a significant challenge to use spider silks in translational research. Shengjie Ling and colleagues review progress in the genetic synthesis of recombinant spider silk proteins (RSSP) and their multiscale self-assembly behaviors, as well as works utilizing multiscale modeling to assist in RSSP material design.…”
mentioning
confidence: 99%